The Influence of Airport Terminal Wayfinding Model on Travellers' Behaviour at Kuala Lumpur International Airport (KLIA) Terminal, Malaysia - Anuar, Nur Khairiel; Sabar, Rohafiz; Ahmad Razimi, Mohd Shahril (ExcelingTech Publishers, 2019)
The purpose of this research is to assess the traveller’s wayfinding behaviour of airport terminal access design. Airport wayfinding is defined as a process in which a traveller makes a decision to navigate using information support systems in order to arrive to destination successfully. Quantitative data is acquired to give meaningful results justifying the research outcomes and allow non-biased interpretation of the research results. It represents the process within the development of the methodology and the concept of airport terminal access design and human wayfinding behaviour. The questionnaire is used to increase the reliability and validity of the research. Respondents who volunteered for the study are chosen among the travellers in airport terminal. The Mean, Standard Deviation (SD) and Two-Way ANOVA test were used to analyse the results and discussed with reference to the general needs as standard design of airport terminal access and take into account the preference of travellers’ general experience. The paper will conclude by suggesting guidelines for airport terminal wayfinding design that will seek to optimise the relative aspirations of all parties concerned. Although many studies have been conducted on wayfinding in general, a detailed evaluation on airport terminal wayfinding design and human wayfinding behaviour in respect of travellers were still unexplored domains